1990
DOI: 10.1017/s0003356100005481
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amount of protein in the concentrates on hay intake and rate of passage, diet digestibility and milk production in British Saanen goats

Abstract: During the first 2 weeks after kidding, 27 multiparous British Saanen goats were offered 1·5 kg hay (98 g crude protein (CP) per kg dry matter (DM)) and from 0·45 increasing to 0·70 kg concentrates (152 g CP per kg DM) daily. Week 2 was used as a covariance period. At week 3 of lactation all the goats were allocated to one of three groups and were offered hay ad libitum and 1 kg concentrates containing 117 (LP), 152 (MP) or 185 (HP) g CP per kg DM daily to week 15. During weeks 4 to 15, hay intake and milk yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
1
2
1
1
Order By: Relevance
“…Indeed, McDonald et al (2002) reported that the apparent digestibility of OM might be as high as 85% in immature pasture grass and as low as 45% in winter herbage. Contrary to the present study, different authors indicated that supplementation could increase digestibility of OM, ADF and DM of which Badamana et al (1990) indicated that increasing CP in concentrates increased the digestibility of OM, ADF and CP. Similarly, Nicholson and Sutton (1969) reported that the apparent digestion coefficient for DM, OM and energy were higher for high concentrate than for high roughage rations both in stomach and in the entire digestive tract.…”
Section: Apparent Digestibility Of Treatment Feedscontrasting
confidence: 99%
“…Indeed, McDonald et al (2002) reported that the apparent digestibility of OM might be as high as 85% in immature pasture grass and as low as 45% in winter herbage. Contrary to the present study, different authors indicated that supplementation could increase digestibility of OM, ADF and DM of which Badamana et al (1990) indicated that increasing CP in concentrates increased the digestibility of OM, ADF and CP. Similarly, Nicholson and Sutton (1969) reported that the apparent digestion coefficient for DM, OM and energy were higher for high concentrate than for high roughage rations both in stomach and in the entire digestive tract.…”
Section: Apparent Digestibility Of Treatment Feedscontrasting
confidence: 99%
“…Achieved losses in body weight of lactating goats are in accordance with the previous research and knowledge about the metabolism in lactating goats [19]. Morand-Fehr et al [20] and Badamana et al [21] concluded that the goats per kidding in the first month of lactation lose 1 kg of the body weight per week, and in the next month, 0.5 kg/week. Body weight losses of goats from the control group were in agreement with these studies.…”
Section: Resultssupporting
confidence: 84%
“…However, most of this increase was clearly only apparent, related to the decreased proportion of faecal metabolic nitrogen in total nitrogen recovered in faeces when the CP content increased (Minson, 1982). The positive effects of protein supplementation on diet digestion have usually been recorded for diets of low digestibility (Badamana et al, 1990;DelCurto et al, 1990) or poor fermentation quality (Jaakkola et al, 1990). The digestibility and fermentation quality of grass silage in this experiment were high.…”
Section: Digestibility Of the Diets And Feed Intakementioning
confidence: 67%